An Interprofessional Approach to Reducing the Risk of Falls Through Enhanced Collaborative Practice. Issue 8 (28th July 2016) - Eckstrom, Elizabeth; Neal, Margaret B.; Cotrell, Vicki; Casey, Colleen M.; McKenzie, Glenise; Morgove, Megan W.; DeLander, Gary E.; Simonson, William; Lasater, Kathie
Abstract : Falls are the leading cause of accidental deaths in older adults and are a growing public health concern. The American Geriatrics Society (AGS) and British Geriatrics Society (BGS) published guidelines for falls screening and risk reduction, yet few primary care providers report following any guidelines for falls prevention. This article describes a project that engaged an interprofessional teaching team to support interprofessional clinical teams to reduce fall risk in older adults by implementing the AGS/BGS guidelines. Twenty‐five interprofessional clinical teams with representatives from medicine, nursing, pharmacy, and social work were recruited from ambulatory, long‐term care, hospital, and home health settings for a structured intervention: a 4‐hour training workshop plus coaching for implementation for 1 year. The workshop focused on evidence‐based strategies to decrease the risk of falls, including screening for falls; assessing gait, balance, orthostatic blood pressure, and other medical conditions; exercise including tai chi; vitamin D supplementation; medication review and reduction; and environmental assessment. Quantitative and qualitative data were collected using chart reviews, coaching plans and field notes, and postintervention structured interviews of participants. Site visits and coaching field notes confirmed uptake of the strategies. Chart reviews showed significant improvement in adoption of all falls prevention strategies except vitamin D supplementation. Long‐term care facilities were more likely to address environmental concerns and add tai chi classes, and ambulatory settings were more likely to initiate falls screening. The intervention demonstrated that interprofessional practice change to target falls prevention can be incorporated into primary care and long‐term care settings.